HUBUNGAN ANTARA KECEPATAN, VOLUME DAN KEPADATAN LALU LINTAS RUAS JALAN SILIWANGI SEMARANG - Nugroho Julianto, Eko (Jurnal Teknik Sipil dan Perencanaan, 2010)
Abstract: The volume of traffic traveling on roads Siliwangi have increased from year to year. ThisisÃÂ  dueÃÂ  toÃÂ  theÃÂ  developmentÃÂ  ofÃÂ  thisÃÂ  area. To overcomeÃÂ  the problemÃÂ  ofÃÂ  trafficÃÂ  congestion onÃÂ  these roadsÃÂ  isÃÂ  requiredÃÂ  priorÃÂ  knowledgeÃÂ  aboutÃÂ  trafficÃÂ  characteristicsÃÂ  andÃÂ  modelÃÂ  ofÃÂ  theÃÂ  relationship between these characteristics. This study aims to analyze the model of the relationship between the characteristic volume (V), speed (S) and density (D)ÃÂ  traffic, in accordance with existing conditions. Survey dataÃÂ  includesÃÂ  traffic volumes and speeds withÃÂ  the manual count method, being analytical modelsÃÂ  includeÃÂ  modelsÃÂ  Greenshield,ÃÂ  Greenberg,ÃÂ  andÃÂ  Underwood.ÃÂ  TheÃÂ  resultsÃÂ  showedÃÂ  thatÃÂ  the relationship model that is suitable for VSD Siliwangi road is to follow the model of Underwood with r = 0859, with the model of Us = 68.20 x exp(-D/-15.05). Keywords: relationship model, Greenshield, Greenberg, Underwood ÃÂ  Abstrak: Volume perjalanan lalu lintas pada ruas jalan Siliwangi mengalami peningkatan dari tahun keÃÂ  tahun.ÃÂ  HalÃÂ  iniÃÂ  disebabkanÃÂ  perkembanganÃÂ  daerahÃÂ  ini.ÃÂ  UntukÃÂ  mengatasiÃÂ  masalahÃÂ  kemacetan lalulintasÃÂ  padaÃÂ  ruasÃÂ  jalanÃÂ  iniÃÂ  terlebihÃÂ  dahuluÃÂ  diperlukanÃÂ  pengetahuan mengenaiÃÂ  karakteristikÃÂ  lalu lintasÃÂ  dan modelÃÂ  hubunganÃÂ  antarÃÂ  karakteristikÃÂ  tersebut. KajianÃÂ  iniÃÂ  bertujuan menganalisis model hubunganÃÂ  antarÃÂ  karakteristikÃÂ  volumeÃÂ  (V),ÃÂ  kecepatanÃÂ  (S)ÃÂ  danÃÂ  kepadatanÃÂ  (D)ÃÂ  laluÃÂ  lintas,ÃÂ  sesuai dengan kondisi yang ada. Survai data meliputi volume dan kecepatanÃÂ  laluÃÂ  lintas dengan metode manualÃÂ  count,ÃÂ  sedangÃÂ  analisis model meliputi modelÃÂ  Greenshield,ÃÂ  Greenberg,ÃÂ  danÃÂ  Underwood. Hasil analisis menunjukkan bahwa model hubungan V-S-D yang sesuai untuk ruasÃÂ  jalan Siliwangi adalah mengikuti model Greenberg dengan nilaiÃÂ  r = 0.773, dengan model Us = 68.20 x exp(-D/-15.05). Kata kunci: model hubungan, greenshield, greenberg, underwood